A Force of Energy Essays in Energy Law in Honour of Professor Martha Roggenkamp - Fleming, Ruven; de Graaf, Kars; Hancher, Leigh; Woerdman, Edwin (University of Groningen Press, 2022)
This book is a Liber Amicorum for Martha Roggenkamp, Professor of Energy Law at the University of Groningen, the Netherlands. The chapters in this book celebrate her unique contribution to energy law. Martha Roggenkamp is a true force of energy, both personally and professionally. Her chair in energy law at the University of Groningen was the first in the Netherlands. She co-established the Dutch Energy Law Association and co-founded the Groningen Centre of Energy Law and Sustainability. With a formidable range of seminal publications, building on a large number of externally funded research projects, and of course her hearty laugh, she is one of the leading women in energy law in the Netherlands, in Europe and beyond. The chapters in this book showcase the diversity of the subject matter, the high academic standards as well as the connections that Martha Roggenkamp has nurtured across decades and continents.